Indication for neoadjuvant chemotherapy in patients with colorectal liver metastases based on a nomogram that predicts disease‐free survival. (25th August 2014) - Okuno, Masayuki; Hatano, Etsuro; Seo, Satoru; Taura, Kojiro; Yasuchika, Kentaro; Nakajima, Akio; Yazawa, Takefumi; Furuyama, Hiroaki; Kawamoto, Hiroshi; Yagi, Shintaro; Nishitai, Ryuta; Fujikawa, Takahisa; et al.
Abstract Background The purpose of this study was to validate the Beppu nomogram, which predicts disease‐free survival (DFS) after resection of colorectal liver metastases, and to investigate the efficacy of neoadjuvant chemotherapy based on the nomogram‐predicted recurrence risk. Methods We retrospectively analyzed 234 patients with colorectal liver metastases who underwent a hepatic resection at eight hospitals between 2005 and 2010. Results The nomogram c‐index of all the patients was 0.59. The observed and the predicted 3‐year DFS showed good agreement. When the patients were divided into two groups who received or did not receive pre‐hepatectomy chemotherapy (PHC), the c‐index of the patients who received PHC was inferior to that of the patients who did not (0.56 and 0.61, respectively). In patients who received PHC, DFS among the quintiles clustered by the nomogram score indicated no significant differences (P = 0.25), unlike in patients who did not receive PHC (P < 0.0001). Surprisingly, in patients with no risk factors for recurrence, neoadjuvant chemotherapy provided significantly lower DFS than no neoadjuvant chemotherapy (3‐year DFS: 42.9% vs. 80.0%, P = 0.03). Conclusions The nomogram validation was shown to be moderately predictive. PHC decreased the performance of the nomogram and might produce no DFS benefit in patients with low recurrent risk.